(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
The hydrogen production is of great importance for various industrial processes and in this context, the WGS reaction is extremely useful to achieve high purity values of this element, especially its use for the recent production of energy in a fuel cell. In this work, nickel-based catalysts were prepared and evaluated in the water gas shift reaction (WGRS). The solids were prepared from nickel, zinc and aluminum nitrate by precipitation techniques. Both the specific surface area and the activity are not affected by small amounts of zinc, but higher amounts of this metal decrease them. In all catalysts, zinc avoids methane production and 100% of selectivity towards carbon dioxide is obtained. During the WGSR, nickel metallic, which is supposed to be the active phase, is produced. The sample with the lowest zinc contend was the most active catalyst in WGSR to produce hydrogen.